2018
DOI: 10.1186/s12864-018-5082-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of RNA-seq and microarray platforms for splice event detection using a cross-platform algorithm

Abstract: BackgroundRNA-seq is a reference technology for determining alternative splicing at genome-wide level. Exon arrays remain widely used for the analysis of gene expression, but show poor validation rate with regard to splicing events. Commercial arrays that include probes within exon junctions have been developed in order to overcome this problem.We compare the performance of RNA-seq (Illumina HiSeq) and junction arrays (Affymetrix Human Transcriptome array) for the analysis of transcript splicing events. Three … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Due to its specific design with specialized junction probes, the HTA2.0 microarray was more sensitive to known splicing events. Specialized junction arrays are generally described to be more performant than RNA-Seq [63]. Detection of differential splicing for RNA-Seq, however, relies on sequencing reads that cover a splicing site by chance [64].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its specific design with specialized junction probes, the HTA2.0 microarray was more sensitive to known splicing events. Specialized junction arrays are generally described to be more performant than RNA-Seq [63]. Detection of differential splicing for RNA-Seq, however, relies on sequencing reads that cover a splicing site by chance [64].…”
Section: Discussionmentioning
confidence: 99%
“…Although RNA-seq, a preferred platform for studying differentially expressed genes and alternative splicing nowadays, has some inherent advantages in comparison with microarrays, such as the ability to identify novel exons and splice junctions in an unbiased manner, the HTA 2.0 platform can nevertheless detect more weakly expressed events, which are missed in the RNA-seq results (Fumagalli et al, 2014 ; Wang et al, 2014 ; Romero et al, 2018 ). Furthermore, the modern microarrays, HTA 2.0, can still outperform RNA-seq for the analysis of gene expression in terms of cost, reproducibility and time as well as memory resources for treating data (Nazarov et al, 2017 ; Romero et al, 2018 ). For these reasons, we have chosen the HAT 2.0 platform as the major research approach for the AS studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, besides RNA-Seq, these data suggested that circRNA microarrays could be an efficient and sensitive tool for the profiling of specific circRNAs in tumor liquid biopsies. Moreover, Romero et al (2018) compared the performance of RNA-Seq and splice junction arrays for the analysis of transcript splicing events in breast cancer cell lines treated with a drug that affects splicing. They observed a high degree of coherence between the two technologies, with the detection power of the junction array being equivalent to RNA-Seq with up to 60 million reads.…”
Section: Discussionmentioning
confidence: 99%